North of nowhere : an Alex McKnight mystery - Hamilton, Steve, 1961- (Hamilton, Steve, 1961- Alex McKnight novel., 2002)
Alex McKnight rarely ventures out from his home these days, even to spend time at his friend Jackie's Glasgow Inn. Even as he lets Jackie force him out one night for a poker game at a stranger's house, Alex is certain it's a bad idea. And when the genial atmosphere rapidly deteriorates, he starts to think maybe he was right. Then three masked, armed robbers burst through the door, and things get a whole lot worse. Soon Alex's three closest friends are implicated in the robbery, and Alex finds himself the object of hostile attention from the victim. As events spin out of control, it becomes clear that somebody is not telling the truth, and has put them all in terrible danger...